2017
DOI: 10.3847/1538-4357/aa6ffa
|View full text |Cite
|
Sign up to set email alerts
|

GMC Collisions as Triggers of Star Formation. III. Density and Magnetically Regulated Star Formation

Abstract: We study giant molecular cloud (GMC) collisions and their ability to trigger star cluster formation. We further develop our three-dimensional magnetized, turbulent, colliding GMC simulations by implementing star formation subgrid models. Two such models are explored: (1) "Density-Regulated," i.e., fixed efficiency per free-fall time above a set density threshold and (2) "Magnetically Regulated," i.e., fixed efficiency per free-fall time in regions that are magnetically supercritical. Variations of parameters a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 64 publications
4
58
1
Order By: Relevance
“…Both the studies came to the conclusion that for smaller clouds slower collisions provided a greater efficiency in forming massive stars. Wu et al (2017b) also studied the collision between molecular clouds with the added support from magnetic fields and found that the star formation rates and efficiencies are higher by a factor of ten in collision simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Both the studies came to the conclusion that for smaller clouds slower collisions provided a greater efficiency in forming massive stars. Wu et al (2017b) also studied the collision between molecular clouds with the added support from magnetic fields and found that the star formation rates and efficiencies are higher by a factor of ten in collision simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Balfour et al (2015Balfour et al ( , 2017) also presented numerical simulation of head-on and non-head-on a cloud-cloud collision. In addition, the magneto-hydrodynamical simulations (MHD) simulation of giant molecular cloud (GMC) collision was carried out by several authors (e.g., Wu et al 2015Wu et al , 2017aWu et al , 2017bChristie et al 2017;Bisbas et al 2017;. They showed GMC collision enhanced star formation rate and efficiency (Wu et al 2017b).…”
Section: Cloud-cloud Collisions As a Trigger Of High-mass Star Formationmentioning
confidence: 99%
“…In addition, the magneto-hydrodynamical simulations (MHD) simulation of giant molecular cloud (GMC) collision was carried out by several authors (e.g., Wu et al 2015Wu et al , 2017aWu et al , 2017bChristie et al 2017;Bisbas et al 2017;. They showed GMC collision enhanced star formation rate and efficiency (Wu et al 2017b). Inoue and Fukui (2013) studied the interface layer of the colliding clouds by three-dimensional MHD simulations, and showed formation of massive molecular cores, which likely lead to form high-mass protostars gaining high mass accretion rate helped by amplified turbulence and magnetic fields via supersonic collision ( see also Inoue et al 2017).…”
Section: Cloud-cloud Collisions As a Trigger Of High-mass Star Formationmentioning
confidence: 99%
“…Proper motion measurements from the final GAIA survey will be also useful to study kinematic substructures in Orion. The degree of kinematic substructure that we measure will also be compared to the results from theoretical/numerical models of star cluster formation under different scenarios (Wu et al 2017a(Wu et al , 2017b.…”
Section: Ppv Connected Structuresmentioning
confidence: 99%